Voltammetric Determination of Ascorbic Acid Content in Cabbage Using Anthraquinone Modified Carbon Paste Electrode - T. Alemu; B Zelalem; N Amare (Journal of Chemistry)
In this study, a low-cost, sensitive, and efficient voltammetric method based on anthraquinone modified carbon paste electrode was developed for determination of ascorbic acid in cabbage samples. After cyclic voltammetry was used to investigate the electrochemical behavior of ascorbic acid and to study dependence of oxidative peak current on scan rate and pH, square wave voltammetric method was developed for direct determination of ascorbic acid in cabbage samples. In contrast to the unmodified carbon paste electrode, a remarkable enhancement in oxidative peak current at anthraquinone modified carbon paste electrode confirmed electrocatalytic property of the modifier towards oxidation of ascorbic acid. A better correlation coefficient for the dependence of peak current on the square root of scan rate (R2=0.9963) than on the scan rate (R2=0.9781) indicated that the oxidation of ascorbic acid at anthraquinone modified carbon paste electrode is predominantly governed by diffusion-controlled process. Square wave amplitude, square wave step potential, and square wave frequency are optimized for the investigation of AA in cabbage. The optimized values are 30 mV, 7 mV, and 35 Hz, respectively. Under the optimized method and solution parameters, an excellent linear response was observed between square wave voltammetric peak current of AQMCPE and concentration of ascorbic acid in the range 5×10−5 to 4×10−3 M with a better correlation coefficient (R2=0.9993) and detection limit (LOD=1.84×10−6 M). The ascorbic acid content of the three cabbage samples from three different cabbage growing areas was found in the range 3.686±0.026–8.298±0.011 mg/g of powdered cabbage. Excellent recovery results between 95.042 and 96.139% for spiked ascorbic acid in cabbage samples confirmed the potential applicability of the developed method based on AQMCPE for the determination of ascorbic acid in real samples like cabbage.